The Effects of Technology Utilization, Public Tax Literacy Level, Tax Service Satisfaction, Tax Service Quality, Tax Sanctions, and Tax Rates on Individual Taxpayer Compliance in Tanjungpinang - Vanesa, Siti Mayawi; Rikayana, Hadli Lidya; Tambunan, Ronia (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the impact of technology utilization, tax literacy, tax service satisfaction, tax service quality, tax sanctions, and tax rates on individual taxpayer compliance in Tanjungpinang. Using a quantitative approach, data were collected from 300 individual taxpayers registered as private sector employees at KPP Pratama Tanjungpinang through random sampling and questionnaires. Multiple linear regression analysis reveals that technology utilization, tax service satisfaction, tax service quality, and tax sanctions significantly affect individual taxpayer compliance, while tax literacy and tax rates do not have a significant partial effect. Simultaneously, all independent variables significantly influence taxpayer compliance. The Adjusted R² of 77.4% indicates that these variables explain most of the variation in individual taxpayer compliance in Tanjungpinang.